Silicon as a Sustainable Option to Increase Biomass With Less Water by Inducing Carbon:Nitrogen:Phosphorus Stoichiometric Homeostasis in Sugarcane and Energy Cane - Teixeira, Gelza Carliane Marques; de Mello Prado, Renato; Rocha, Antonio Márcio Souza; de Cássia Piccolo, Marisa (Frontiers in Plant Science, 2022)
Climate change has prolonged periods of water deficit in sugarcane and energy cane crops. This condition induces an imbalance of the carbon (C): nitrogen (N): phosphorus (P) stoichiometric homeostasis, impairing accumulated nutrients from being converted into biomass. Silicon (Si) supplementation can mitigate the damage caused by water deficit in plants by improving the C:N:P balance, increasing C, N, and P use efficiencies and the biomass conversion, and reducing climate change effects on crops. This study assesses the beneficial effects of Si applied through fertigation associated with foliar spraying on the alleviation of damage caused by severe water deficit in sugarcane and energy cane for intermediate and long periods. In addition, the effects in maintenance of nutritional homeostasis we assessed and C, N, and P use efficiencies on sugarcane and energy cane under those conditions were increased. Four experiments were conducted during the first growth cycle of each species. The effect of fertigation associated with Si foliar spraying was evaluated by applying Si only during the seedling formation phase in sugarcane and energy cane grown under severe water deficit for 60 days after transplanting (intermediate period). Then, the effect of Si applied during seedling formation and supplemented after transplanting was evaluated in sugarcane and energy cane grown under severe water deficit for 160 days after transplanting (long period). The Si supply decreased C contents, modified the C:N:P ratio, and increased C, N, and P use efficiencies in plants of both species under water deficit at the intermediate and long periods after transplanting. The effects of applying Si through fertigation associated with foliar spraying during seedling formation mitigated the damage caused by severe water deficit in the intermediate period, which was mainly observed in sugarcane. When supplemented with Si after transplanting, the mitigating effects occurred in both species under severe long period water deficit. Therefore, the Si supply through fertigation associated with foliar spraying is a viable alternative to provide Si to the plant. It also comes with beneficial effects that partially reverse the damage to nutritional homeostasis and increase nutritional efficiency in plants under severe water deficit.